Polymorphic variant rs1739843 of heat shock protein beta-7 (HSPB7) gene and its relationship with on clinical profile and outcomes in patients with hypertrophic cardiomyopathy (results of a 10-year follow-up) - A. A. Streltsova; A. Y. Gudkova; A. A. Poliakova; S. A. Pyko; A. A. Kostareva (Российский кардиологический журнал)
Aim. To determine the impact of polymorphic variant rs1739843 of the HSPB7 gene on clinical profile and outcomes in patients with hypertrophic cardiomyopathy (HCM).Material and methods. The study population consisted of 108 patients with HCM ≥45 years old. The control group included 192 healthy donors. The design of the study included an assessment of the clinical course, determining the outcome of HCM using a new methodological approach proposed by Rowin EJ, et al. (2017). Polymorphic variant rs1739843 of the HSPB7 gene was genotyped by allele-specific real-time polymerase chain reaction (PCR) assay.Results. It was found a significant increase in frequency of TT genotype of rs1739843 of the HSPB7 gene in patients with HCM — 20,4%, compared with control group — 4,2% (ТТ: ТС+СС, odds ratio (OR) =5,88, 95% confidence interval (CI) =2,52-13,75, p<0,001). High prevalence of CC genotype of rs1739843 of the HSPB7 gene was observed in control group — 80,2% vs 31,5% in HCM group (CC: ТС+TT, OR=0,11, 95% CI=0,07-0,19, p<0,001). The allele frequency (С:Т) also differs between HCM and control groups — 55,6:44,4% in HCM vs 88,02:11,98% in control group (OR=5,88, 95% CI=3,91-8,85, p<0,001). It was also found a significant increase in frequency of TT genotype and T allele of rs1739843 of the HSPB7 gene in HCM patients with oligosymptomatic HCM course — 16,7%, compared with control group — 4,2% (ТТ: ТС+СС, OR=4,60, 95% CI=1,63-12,99, p<0,001). HCM patients ≥45 years old showed a significant increase in T allele frequency in cases of presence of 2 (FC III-IV CHF (chronic heart failure)+AF (atrial fibrillation), 18,8% vs 6,6%) and 3 adverse pathways (FC III-IV CHF+AF+SCD (sudden cardiac death), 4,2% vs 1,6%).Conclusion. HCM progression along 2 and more adverse pathways in patients ≥45 years old has been characterized with adverse outcome. The T allele and TT genotype of rs1739843 of the HSPB7 gene were more frequent in patients with HCM ≥45 years old, compared with control group. It was also found a significant increase in frequency of TT genotype and T allele of rs1739843 of the HSPB7 gene in HCM patients with oligosymptomatic HCM course, compared with control group.Allele T of rs1739843 of the HSPB7 gene is associated with 2 and more adverse pathways of HCM progression.